A comparative study on the efficiency of K-file, K-flex and hedstrom files for the apical preparation of curved mesiobuccal canals of human mandibular molars - Nable, Ma. Carmen A.; Santos, Aimee Grace B.; Sison, Sarah S.; Jimena, Edna M. +(Adviser).
The purpose of this study was to compare the abilities of K-File, K-Flex and Hedstrom files in preparing curved canals. Thirty-three curved mesiobuccal root canals of human mandibular first or second molars were equally divided into three groups. Each group corresponded to a type of file. The canals were prepared using the Modified Flaring Recapitulation Technique. Pre- and post-operative radiographs of the canals were taken and the teeth were sectioned at a and 4 mm. levels from the apex. Three Endodontists were then made to evaluate the radiographs and cross sections for extent of apical transportation, alteration in preparation length, canal shape and centering ability of the file. It was concluded in this study that there was no significant statistical difference between the abilities of K-Flex, F-File and Hedstrom files in dealing with curved canals. It is the technique with which the file is handled that determines the outcome of the curved root canal. The modified flaring recapitulation technique was also evaluated and its showed low incidene of plugging, good file centering ability and a predominance of rounded canal shapes.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Endodontics